JAK2 mediates lung fibrosis, pulmonary vascular remodelling and hypertension in idiopathic pulmonary fibrosis: an experimental study. Issue 6 (10th February 2018) - Milara, Javier; Ballester, Beatriz; Morell, Anselm; Ortiz, José L; Escrivá, Juan; Fernández, Estrella; Perez-Vizcaino, Francisco; Cogolludo, Angel; Pastor, Enrique; Artigues, Enrique; Morcillo, Esteban; Cortijo, Julio
Abstract : Background: Pulmonary hypertension (PH) is a common disorder in patients with idiopathic pulmonary fibrosis (IPF) and portends a poor prognosis. Recent studies using vasodilators approved for PH have failed in improving IPF mainly due to ventilation ( V )/perfusion ( Q ) mismatching and oxygen desaturation. Janus kinase type 2 (JAK2) is a non-receptor tyrosine kinase activated by a broad spectrum of profibrotic and vasoactive mediators, but its role in PH associated to PH is unknown. Objective: The study of JAK2 as potential target to treat PH in IPF. Methods and results: JAK2 expression was increased in pulmonary arteries (PAs) from IPF (n=10; 1.93-fold; P=0.0011) and IPF+PH (n=9; 2.65-fold; P<0.0001) compared with PA from control subjects (n=10). PA remodelling was evaluated in human pulmonary artery endothelial cells (HPAECs) and human pulmonary artery smooth muscle cells (HPASMCs) from patients with IPF in vitro treated with the JAK2 inhibitor JSI-124 or siRNA-JAK2 and stimulated with transforming growth factor beta. Both JSI-124 and siRNA-JAK2 inhibited the HPAEC to mesenchymal transition and the HPASMCs to myofibroblast transition and proliferation. JAK2 inhibition induced small PA relaxation in precision-cut lung slice experiments. PA relaxation was dependent of the large conductance calcium-activated potassium channel (BKCa ). JAK2 inhibition activated BKCa channels and reduced intracellular Ca 2+ . JSI-124 1 mg/kg/day, reduced bleomycin-induced lung fibrosis, PA remodelling, right ventricular hypertrophy, PA hypertension and V / Q mismatching in rats. The animal studies followed the ARRIVE guidelines. Conclusions: JAK2 participates in PA remodelling and tension and may be an attractive target to treat IPF associated to PH.